Progressive retinal atrophy in Shetland sheepdog is associated with a mutation in the CNGA1 gene. (22nd July 2015) - Wiik, A. C.; Ropstad, E. O.; Ekesten, B.; Karlstam, L.; Wade, C. M.; Lingaas, F.
Summary Progressive retinal atrophy (PRA) is the collective name of a class of hereditary retinal dystrophies in the dog and is often described as the equivalent of retinitis pigmentosa in humans. PRA is characterized by visual impairment due to degeneration of the photoreceptors in the retina, usually leading to blindness. PRA has been reported in dogs from more than 100 breeds and can be genetically heterogeneous both between and within breeds. The disease can be subdivided by age at onset and rate of progression. Using genome‐wide association with 15 Shetland Sheepdog (Sheltie) cases and 14 controls, we identified a novel PRA locus on CFA13 (Praw = 8.55 × 10−7, Pgenome = 1.7 × 10−4). CNGA1, which is known to be involved in human cases of retinitis pigmentosa, was located within the associated region and was considered a likely candidate gene. Sequencing of this gene identified a 4‐bp deletion in exon 9 (c.1752_1755delAACT), leading to a frameshift and a premature stop codon. The study indicated genetic heterogeneity as the mutation was present in all PRA‐affected individuals in one large family of Shelties, whereas some other cases in the studied Sheltie population were not associated with this CNGA1 mutation. To our knowledge, this is the first report of a mutation in CNGA1 causing PRA in dogs.